2008
DOI: 10.1007/s11999-007-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Ion Release Differ Between Hip Resurfacing and Metal-on-metal THA?

Abstract: Modern metal-on-metal hip resurfacing was introduced as a bone-preserving method of joint reconstruction for young and active patients; however, the large diameter of the bearing surfaces is of concern for potential increased metal ion release. We hypothesized there were no differences in serum concentrations of chromium, cobalt, and molybdenum between patients who had metalon-metal hip resurfacing (Group A; average head diameter, 48 mm; median followup, 24 months) and patients who had 28-mm metal-on-metal THA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 44 publications
(40 reference statements)
3
25
0
Order By: Relevance
“…Although there are no published reports which directly compare ion levels in patients with MOM-BHR or MOM-THA, our data are in the range previously reported. Some authors have evaluated ion levels, but the studies either had short-term followup or they were not comparative studies of MOM-BHR versus MOM-THA (Table 4) [3,5,11,17,27,29,34,38,39]. In addition, we found time of followup and age had no influence on serum ion levels, whereas gender in association with implant type influenced Cr levels, with females who had MOM-BHR showing an increase in Cr levels compared with males who had MOM-BHR.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although there are no published reports which directly compare ion levels in patients with MOM-BHR or MOM-THA, our data are in the range previously reported. Some authors have evaluated ion levels, but the studies either had short-term followup or they were not comparative studies of MOM-BHR versus MOM-THA (Table 4) [3,5,11,17,27,29,34,38,39]. In addition, we found time of followup and age had no influence on serum ion levels, whereas gender in association with implant type influenced Cr levels, with females who had MOM-BHR showing an increase in Cr levels compared with males who had MOM-BHR.…”
Section: Discussionmentioning
confidence: 74%
“…Theoretical and experimental studies, however, suggest metal wear may increase serum metal ion levels, which would be a cause for concern, particularly in the long term. A previous short-term study suggested that there were no differences in metal ion concentrations between large-diameter MOM-BHR bearings and small-diameter MOM-THA bearings [27]. Data from the same comparison at medium term are lacking.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This was expected because the bearing characteristics of the two acetabular components were identical and the manufacturing tolerances for roundness and clearance were the same. In addition, the median values for serum cobalt and chromium were as low as any previously reported for any type of hip resurfacing design [1,16,21,22,28].…”
Section: Discussionmentioning
confidence: 50%
“…Laboratory results [1,37] and clinical metal ion [3,12,31] studies relating to the effect of bearing diameter on wear and metal ions suggest conflicting conclusions, with some showing an inverse relationship between bearing diameter and wear and others showing no effect. Several in vitro studies relating to the effect of clearance [14,20,35,36] on wear also reported conflicting results.…”
Section: Introductionmentioning
confidence: 99%